The Effect of Variation of Raw Material Ratio on Hydrogel Based on K-Carrageean - Acrylamide as a Carrier of Ammonium Nitrate Fertilizer - Hendrawan Laksono; Mersi Kurniati; Yessie Widya Sari; Christina Winarti (Dept. of Chemical Engineering, Diponegoro University, 2021)
Hydrogels based on natural polymers such as carrageenan are currently being developed to improve efficiency in agriculture. By enriching hydrogels with fertilizers, they will be released slowly into the soil. Enrichment of fertilizers on carrageenan-based hydrogels was carried out and analyzed with the response of swelling ability, gel fraction value of grafting degree, to the hydrogel's ability to release the fertilizer trapped in it. Carrageenan is used because its use as a natural polymer has not been widely explored, especially in the non-food sector. The results showed that the average swelling value of carrageenan-based hydrogel to ammonium nitrate solution ranged from 750.00% - 1,633.33%. The gel fraction values obtained ranged from 74.06% to 87.51%, and the degree of grafting ranged from 85.33% to 93.59%. These values indicate a relatively high degree of tissue density and grafting of acrylamide monomer on carrageenan, which means that the carrageenan:AAm based hydrogel has strong mechanical properties. The ability to release ammonium nitrate samples from the hydrogel carrageenan-based has a value ranging from 8.86% to 44.92% in five days of observation. Interpretation of the test results, the best ratio of carrageenan:AAm is 1:1, due to its relatively low release value but still has good swelling and mechanical properties.Keywords: Hydrogel; Carrageenan; Acrilamyde; Fertilizer release